Analysis of the influence of the length of beech sawlogs (Fagus sylvatica L.) on the maximum quantity exploitation - Rabadziski, Branko; Zlateski, Goran; Krstev, Marija; Stamenkoska, Ana-marija (Faculty of Design and Technologies of Furniture and Interior - Skopje, 2021)
More than two decades have passed since scientific research was done on the influence of the length of beech sawlogs on the maximum quantity exploitation, so therefore there is no new data on this topic. For this particular aim, an analysis was done regarding beech sawlogs, a wood species that dominate this region in sawmill technology and processing. The analyzed logs were graded according to the European grading standard. The logs were inherent to the Ist and IInd quality class. The sawlogs were with the length of 2,0; 3,0 and 4,0 m. The sawlogs with a length of 2,0 m were with a measured diameter at a range from 31,0 to 52,0 cm, at the narrower end of the log, and on the wider end from 32,0 to 53,0 cm. There were 15 analyzed logs with a wood mass of 4,2 The logs with the length of 3,0 m were with a measured diameter at a range from 33,0 to 50,0 cm, at the narrower end of the log, and on the wider end from 35,0 to 54,0 cm. The analysis covered 15 logs with a wood mass of 6,5 The logs with the length of 4,0 m were with a measured diameter at a range from 35,0 to 52,0 cm, at the narrower end of the log, and on the wider end from 39,0 to 56,0 cm. The number of analyzed logs was 15. The wood mass of the logs was 8,9 The total count of analyzed logs was 45 and the amount of processed wood mass was approximately 22,0 The log diameter taper (S) of analyzed logs was as follows:  for the length of l = 2,0 m → 0,5 ÷ 1,0 cm/m, Ssr = 0,54 cm/m, logs with a great mass;  for the length of l = 3,0 m → 0,66 ÷ 1,33 cm/m, Ssr = 1,01 cm/m, logs with a full mass;  for the length of l = 4,0 m → 0,75 ÷ 1,5 cm/m, Ssr= 1,23 cm/m, logs with a poor mass. Maximum quantity exploitation (P) of the different lengths of the logs was as follows:  for the length of l = 2,0 m → P = 66,60 ÷ 68,32 %, Psr = 67,26 %;  for the length of l = 3,0 m → P = 64,20 ÷ 66,99 %, Psr = 65,16 %;  for the length of l = 4,0 m → P = 61,07 ÷ 62,53 %, Psr = 61,10 %.
Keywords: logs; beech; sawmill; measurements; quality class; sawn lumber; quantity exploitation